2013
DOI: 10.1177/1524838013515761
|View full text |Cite
|
Sign up to set email alerts
|

Using Cognitive Theory and Methodology to Inform the Study of Sexual Victimization

Abstract: Sexual victimization is a prevalent problem among college-aged women. In order to investigate the mechanisms underlying sexual victimization, researchers have focused on the role of cognitive processes such as perception of sexual victimization risk, positing that difficulties with risk perception heighten women's risk for victimization. However, researchers generally have not conceptualized risk perception in the context of a comprehensive cognitive model or utilized tasks and stimuli that allow them to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Women balance a complex set of cognitive and emotional factors when perceiving and acting during a sexual assault (Norris et al, 1996; Nurius & Norris, 1996). Future research could include an examination of multiple scenarios to account for potential situational differences that may impact sexual assault risk perception as suggested by Rinehart and Yeater (2015). Future research could also include alcohol administration studies examining the synergistic effects of both ASA history and acute alcohol intoxication on sexual assault risk perception.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Women balance a complex set of cognitive and emotional factors when perceiving and acting during a sexual assault (Norris et al, 1996; Nurius & Norris, 1996). Future research could include an examination of multiple scenarios to account for potential situational differences that may impact sexual assault risk perception as suggested by Rinehart and Yeater (2015). Future research could also include alcohol administration studies examining the synergistic effects of both ASA history and acute alcohol intoxication on sexual assault risk perception.…”
Section: Discussionmentioning
confidence: 99%
“…The use of multiple methods to examine sexual assault risk perception may also help further understanding of these associations due to their complicated nature. A review (Rinehart & Yeater, 2015) indicated that simply asking women when they may leave a situation may not adequately assess risk perception because although women may be sensitive to cues, they may not leave the situation. Behavioral intent indicating when there are enough risk cues present to leave a potentially risky situation or when one cue is risky enough to leave can be one type of sexual assault risk perception.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also worth noting that deficits in risk detection in women with sexual assault victimization histories are not always observed (for a review, see Gidycz et al, 2006). To explain the inconsistent findings regarding risk detection deficits in prior sexual assault victims, Rinehart and Yeater (2015) suggest that it is important to distinguish between risk detection (identifying a situation as risky) and decision-making (acting on that risk). Many studies of victimization history and risk detection fail to distinguish properly between these two constructs.…”
Section: Discussionmentioning
confidence: 99%
“…One relatively unexplored factor related to prosocial bystander behavior is sexual assault victimization (SAV) experiences, which can have a unique influence on risk recognition-a key component of bystander intervention (e.g., Bridges et al, 2020;Ham et al, 2019). For instance, some researchers have found that having an SAV experience can decrease risk recognition (Gidycz et al, 2006;Neilson et al, 2018;Rinehart & Yeater, 2015;Wilson et al, 1999), increase risk recognition (Gidycz et al, 2006;Untied et al, 2012) or have no effect on it (Gidycz et al, 2006;Yeater et al, 2009). Given these mixed findings, the influence that SAV experiences may have on women's bystander behaviors is difficult to determine.…”
Section: Sexual Assault Victimizationmentioning
confidence: 99%